Teori al-Maslahah dan Aplikasinya dalam Norma Kriminalisasi Undang-Undang Antikorupsi - Asmawi Asmawi (Universitas Islam Negeri Jakarta, 2013)
Abstract: The Theory of al-Maslahah and its Application in Criminalization Norms of the Law on Anti-Corruption. This study demonstrates that the theory of al-maslahah has been applied in criminalization norms of the law on corruption eradication, namely in the criminalization norms of corruption related to a country’s finances or economy and the criminalization norms of corruption related to bribery. It can be concluded that the existence of such relevance carries the implication that the norms of Islamic criminal law have undergone a transformation or objectification through the application of al-maslahah into an arrangement of national criminal laws, which are represented by anti-corruption criminal law. The existence of such relevance also carries an implication that the anti-corruption criminal law has undergone Islamization through the application of al-maslahah, especially within the criminalization norms that are contained in it. In other words, the criminal law on anti-corruption in Indonesia is Islamic or has validity shar‘î, because it pervades the norms of Islamic criminal law through the application of the theory of al-maslahah.Keywords: al-maslahah, criminalization, corruption, ta‘zîrAbstrak: Teori al-Maslahah dan Aplikasinya dalam Norma Kriminalisasi Undang-Undang Antikorupsi. Studi ini membuktikan bahwa teori al-maslahah telah teraplikasikan dalam norma kriminalisasi undang-undang pemberantasan tindak pidana korupsi, yakni dalam norma kriminalisasi korupsi terkait keuangan atau perekonomian negara dan norma kriminalisasi korupsi terkait suap-menyuap. Dapat disimpulkan pula bahwa adanya relevansi yang demikian membawa implikasi bahwa norma hukum pidana Islam telah mengalami transformasi atau objektivikasi melalui aplikasi al-maslahah ke dalam tatanan hukum pidana nasional, yang direpresentasikan hukum pidana antikorupsi. Adanya relevansi yang demikian juga membawa implikasi bahwa hukum pidana antikorupsi telah mengalami islamisasi melalui aplikasi al-maslahah, terutama dalam norma-norma kriminalisasi yang dikandungnya. Tegasnya, hukum pidana antikorupsi di Indonesia sudah islami atau punya validitas shar‘î karena sudah menyerap norma hukum pidana Islam melalui aplikasi teori al-maslahah.Kata Kunci: al-maslahah, kriminalisasi, korupsi, takzirDOI: 10.15408/ajis.v13i2.929